TINJAUAN PENGARUH PERUBAHAN TUTUPAN LAHAN TERHADAP PARAMETER CUACA - Fani Setyawan; Muhammad Dimyati (Universitas Negeri Padang, 2023)
This paper reviews the relationship between land cover changes and weather parameter conditions in an area. By using the literature review method, it is expected to be able to provide an explanation regarding changes in air temperature conditions, surface wind circulation and rainfall patterns due to changes in land cover. The expansion of urban areas and an increase in built-up land has led to the formation of Urban Heat Island (UHI) where the surface air temperature becomes hotter than the surrounding area. Topography and changes in the vegetation landscape can affect the surface wind circulation patterns and, in some places, reduce the speed due to surface roughness. Various numerical simulations have also shown that changes in land cover can increase the amount of rainfall in an area, but in nearby areas the amount of rainfall can decrease. From various studies that have been carried out, changes in land cover have a strong influence in changing the condition of weather parameters in an area.